Stress Management Health Education and Relaxation Therapy Training for Children and Adolescents in Saint Beatrix Orphanage Sidoarjo - Anindya Arum Cempaka; Ira Ayu Maryuti; Abigael Grace Prasetiani (Universitas Lambung Mangkurat, 2022)
The Covid-19 pandemic has become a stressful situation for teenagers and children, thus affecting their health and immune system. Prolonged stress (chronic stress) impacts the body's immune system. Stress has an emotional, cognitive, physiological, and behavioural impact. Individuals with high-stress levels will have more difficulty manifesting positive thoughts, emotions, and behaviours. Good mental health is essential for a person to deal with stress in life and is vital in the physique health of adults and children. Therefore, community service was carried out to help with stress management and relaxation therapy. This community service aims to reduce stress among children and adolescents in Saint Beatrix orphanage Sidoarjo. This program involved thirty female children and adolescents in Saint Beatrix orphanage Sidoarjo. They took a pre-test, which indicated a low knowledge of stress management. The results showed that the participants had poor knowledge about stress management. Methods used for stress management education were lectures and discussions. Evaluation of the program successfully before and after the activity was measured after the participants filled out a questionnaire that measured their knowledge about stress management. Meanwhile, the evaluation of relaxation therapy training was carried out through demonstration. After conducting the program, it showed that the number of participants with a high level of knowledge went up to 77%. Based on the Wilcoxon Sign Rank Test result, it's known that the p-value = 0,000 with (ɑ<0.05), which means this program may enhance participants’ knowledge.